Pemberian Pendampingan Pada Balita Dengan Masalah Gizi Di Kelurahan Sidodadi - Sulfah, Talitha; Elvandari, Milliyantri; Mawary, Mara (Journal Of Human And Education (JAHE), 2024)
Stunting is a serious global health problem, especially in developing countries, including Indonesia. Stunting assistance is an important strategy in overcoming this problem. This assistance aims to help overcome the problem of stunting in the city of Surabaya. The mentoring method which involves 3 stages, namely: searching for toddler data, implementation, monitoring and evaluation has proven to be effective in increasing children's growth. The research results show that sustainable stunting assistance has a significant positive impact on children's growth and development. However, challenges such as health service accessibility, public awareness, and program sustainability remain the main focus. Therefore, the implementation of a broader, more coordinated and sustainable stunting assistance program is needed to address the stunting problem in a comprehensive and sustainable manner.